A model for preservice teachers' intentions to use ICT in future lessons†. Issue 7 (3rd October 2017) - Baydas, Ozlem; Goktas, Yuksel
ABSTRACT: This study proposes a model for determining preservice teachers' intentions to use information and communication technology (ICT) in future lessons. Data were collected from 21 preservice teachers via interview in the first stage of the study and from 2904 preservice teachers from 16 different universities via a designed scale in the second stage of the study. Data were analyzed through structural equation modeling. A model capable of explaining 85% of variance in preservice teachers' intentions to use ICT in their future lessons was developed. Perceived usefulness (PU) was seen to have the highest influence on their intentions, while facilitating conditions, social influence, and anxiety had a low direct effect. In addition, these factors were found to have a high indirect influence on intention through other factors such as PU, perceived ease-of-use, and efficacy. Abbreviations: ICT: information and communication technology; M: mean; SD: standard deviation; SEM: structural equation modeling